2004
DOI: 10.1097/01.brs.0000127184.43765.61
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Interobserver Agreement for Determinations of Rabbit Posterolateral Spinal Fusion

Abstract: Both radiographic techniques used in the study recorded high sensitivity and negative predictive value. However, positive predictive value was poor, especially with fine detail radiographs. Nevertheless, CT with reformatted images did appear to be superior to fine detail radiographs in accurately identifying nonunions in this animal model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 25 publications
1
40
0
5
Order By: Relevance
“…These investigators also demonstrated that evaluation of fusion by manual palpation correlated more closely with biomechanical test results than did radiographic evaluation [31]. This concept is also supported by data from other studies [21,[32][33][34]. Although some studies have suggested that radiographs underestimate the actual fusion rate [28,35], our results appear to support the notion that plain radiographic assessment of fusion can be an overestimation of actual fusion rates.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These investigators also demonstrated that evaluation of fusion by manual palpation correlated more closely with biomechanical test results than did radiographic evaluation [31]. This concept is also supported by data from other studies [21,[32][33][34]. Although some studies have suggested that radiographs underestimate the actual fusion rate [28,35], our results appear to support the notion that plain radiographic assessment of fusion can be an overestimation of actual fusion rates.…”
Section: Discussionsupporting
confidence: 87%
“…The aim of this study was to achieve a fusion rate of less than 40 % and then determine whether autologous bone marrow augmented arthrodesis. Other studies subsequently used this bone paucity model to provide a larger potential for improved fusion rates with a variety of bone graft substitutes [13][14][15][16][17][18][19][20][21][22]. While our study found a significant positive relationship between volume of autograft and fusion rates, a tenfold range of volume of autograft (1.4-12 cm 3 ) was used in the studies evaluated.…”
Section: Discussionmentioning
confidence: 78%
“…Many patients are now on therapeutic regimens directed at altering the balance between bone formation and bone resorption with a goal of influencing bone mineral density, and hence, fracture risk. Bisphosphonates and selective estrogen modulators have been investigated extensively 12,36,44) . Bisphosphonates have been used therapeutically for the last three decades to treat variety of metabolic bone disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Because of this, we could compare our results only with the studies which had been used aledronate. Many investigators consider manual palpation as the gold standard in fusion assessment in animal models 5,44) . In the present study, 69% of specimens in control group and 46% of specimens in risedronate group were thought to have a solid fusion by manual palpation and it was not found to be statistically significant (p = .251).…”
Section: Discussionmentioning
confidence: 99%
“…However, plain radiography has a disadvantage in that the radiograph is easily misinterpreted when evaluating whether the fusion mass is solid or not [1,[6][7][8]. This problem is compounded by the use of ceramic composite because of its marked relative density [9].…”
Section: Introductionmentioning
confidence: 99%